PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE ROTATING TRIO EXCHANGE BERBANTUAN MIND MAPPING TERHADAP HASIL BELAJAR - Gandara Muhammad Faradias Manggala; Yoni Hermawan; Rendra Gumilar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this research is to be able to improve students' learning outcomes through a cooperative learning model of rotating trio exchange type assisted by mind mapping. The research method used was a quasi-experiment with a quantitative approach with a research design of nonequivalent control group design. The results showed that the cooperative learning model type rotating trio exchange assisted by mind mapping had an effect in improving students' learning outcomes and was more effective than the conventional learning model. This is based on the results of the independent sample t-test and descriptive analysis which shows that the increase in experimental learning outcomes using the cooperative learning model type rotating trio exchange assisted by mind mapping is higher than the control class using the conventional learning model.